Aggregation behavior of Perfluorononanoic Acid/Sodium Dodecyl sulfate mixtures - Torres, María Florencia (2013)
The mixed system of an anionic hydrocarbon surfactant, sodium dodecyl sulfate, and a perfluorinated surfactant, perfluorononanoic acid (PFNA), was investigated by a combination of methods. The critical micellar concentrations (CMC) were determined over a wide range of sample compositions by surface tension, conductivity and UV–visible spectrophotometry using N-(4-nitrophenyl)perfluorononanamide as a molecular probe. The values of CMC obtained by different techniques were in good agreement. In addition, the aggregation numbers were determined in the mixtures with a low content of hydrocarbon surfactant, by measuring the fluorescence quenching of pyrene. The hydrodynamic radii of the aggregates were estimated through the diffusion ordered 19F- and 1 H-NMR spectroscopy. The values obtained are in agreement with those expected according to the measured aggregation numbers. The analysis of the data with different aggregation models suggests the formation of a nonideal mixed micelle that is enriched in the perfluorinated surfactant when its mole fraction increases, and that is practically formed by PFNA only at mole fractions higher than 0.8.